2019
DOI: 10.1038/s41598-019-48609-z
|View full text |Cite
|
Sign up to set email alerts
|

S1P2 contributes to microglial activation and M1 polarization following cerebral ischemia through ERK1/2 and JNK

Abstract: Sphingosine 1-phosphate (S1P) signaling has emerged as a drug target in cerebral ischemia. Among S1P receptors, S1P 2 was recently identified to mediate ischemic brain injury. But, pathogenic mechanisms are not fully identified, particularly in view of microglial activation, a core pathogenesis in cerebral ischemia. Here, we addressed whether microglial activation is the pathogenesis of S1P 2 -mediated brain injury in mice challenged with transient middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 62 publications
1
52
0
Order By: Relevance
“…It has been shown that the S1P 2 is more abundantly expressed on vascular endothelial cells after cerebral ischemia [ 17 ], involved in vascular permeability and inflammation [ 59 , 60 ] with potential influence on lymphocyte traffic to and within the brain [ 61 ]. Moreover, S1P 2 was recently linked to a pro-inflammatory response by inducing M1 polarization after cerebral ischemia [ 62 ]. In contrast, S1P 3 is expressed in embryonic endothelial cells and is required for endothelial cell morphogenesis as well as migration [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the S1P 2 is more abundantly expressed on vascular endothelial cells after cerebral ischemia [ 17 ], involved in vascular permeability and inflammation [ 59 , 60 ] with potential influence on lymphocyte traffic to and within the brain [ 61 ]. Moreover, S1P 2 was recently linked to a pro-inflammatory response by inducing M1 polarization after cerebral ischemia [ 62 ]. In contrast, S1P 3 is expressed in embryonic endothelial cells and is required for endothelial cell morphogenesis as well as migration [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cerebral ischemia, S1P2 mediates ischemic brain injury [132]. Inhibition of S1P2 resulted in the restoration of the ramified morphology of microglia, reduced proliferation and reduction of the M1 marker NF-κB, suggestively by reducing phosphorylation levels of ERK1/2 and JNK, but not Akt and p38 MAPK [133].…”
Section: Microgliamentioning
confidence: 99%
“…Microglia activation by lipopolysaccharide stimulation is associated with downregulation of S1PR1 and without any change in S1PR2 and S1PR3 [104]. Recent data indicate that S1PR1-3 are associated with M1 microglial polarization in the ischemic brain by regulating ERK1/2, JNK, p38 MAPKs, and Akt [105][106][107]. S1PR5 is preferentially expressed in oligodendrocytes [108].…”
Section: S1pr In Nervous Systemmentioning
confidence: 99%